First MOOC internet courses in Lithuania: learning quality and the importance of learning objects - Gudonienė, Daina; Rutkauskienė, Danguolė (Information & Media, 2015)
The article presents the MOOC international experience and the first initiative steps taken in Lithuania. The Kaunas University of Technology lecturers in 2014 proposed the first MOOCs in the Lithuanian language, which gained a huge success among participants (2009 participants in total). This article investigates the course modelling techniques, advantages and disadvantages, the course participants address the opinion about their essential stages. As we already know, MOOC (liet. MAIK) gained a huge success in international society, which stimulated a significant discussion about the revolution in high education. The main problem is how to ensure the quality in developing and presenting MOOCs, what are the main course elements ensuring the qualitative MOOC development. For this purpose, the usage of open education resources in education is greatly encouraged. Open source tools and elements, various open information resources are used, and all participants willing to learn are registered. In order to ensure the successful learning process, a well-established course structure, learning objects, properly selected tools are needed. The aim of the research is to present the results and to analyze data provided by participants of the first Lithuanian MOOC “Information Technology”.